2017
DOI: 10.1016/j.wem.2016.12.011
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic Acetaminophen or Ibuprofen Result in Equivalent Acute Mountain Sickness Incidence at High Altitude: A Prospective Randomized Trial

Abstract: We found little evidence of any difference between acetaminophen and ibuprofen groups in AMS incidence. This suggests that AMS prevention may be multifactorial, affected by anti-inflammatory inhibition of the arachidonic-acid pathway as well as other analgesic mechanisms that mediate nociception. Additional study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…44 Another study claimed to show benefit, but the trial did not include a placebo arm and instead compared the incidence of AMS with ibuprofen with historically reported rates from the region in which the study was conducted. 45 Although no studies have compared ibuprofen with dexamethasone, 2 studies have compared ibuprofen with acetazolamide. The first found an equal incidence of high altitude headache and AMS in the acetazolamide and ibuprofen groups, with both showing significant protection compared to placebo.…”
Section: Ibuprofenmentioning
confidence: 99%
“…44 Another study claimed to show benefit, but the trial did not include a placebo arm and instead compared the incidence of AMS with ibuprofen with historically reported rates from the region in which the study was conducted. 45 Although no studies have compared ibuprofen with dexamethasone, 2 studies have compared ibuprofen with acetazolamide. The first found an equal incidence of high altitude headache and AMS in the acetazolamide and ibuprofen groups, with both showing significant protection compared to placebo.…”
Section: Ibuprofenmentioning
confidence: 99%
“…Finally, both steroids and nonsteroidal anti-inflammatory drugs (NSAIDS) equally reduce AMS incidence despite their different modes of action ( Dumont et al, 2000 ; Gertsch et al, 2012 ; Zheng et al, 2014 ). This suggests that both COX-2 mediated inflammation as well as analgesic mechanisms that mediate nociception contribute to AMS symptomology ( Hartmann et al, 2000 ; Song et al, 2016 ; Kanaan et al, 2017 ). Indeed, inflammatory mediators released during tissue injury can activate nociceptors and can contribute to pain hypersensitivity ( Kidd and Urban, 2001 ).…”
Section: Pathophysiological Consequencesmentioning
confidence: 99%
“…Accordingly, Dumont et al (2000) showed a reduction in AMS incidence and severity with anti-inflammatory drug treatment. Both steroids and non-steroidal anti-inflammatory drugs reduced the incidence of AMS, despite their different mechanisms of action (Gertsch et al, 2010(Gertsch et al, , 2012Kanaan et al, 2017;Lipman et al, 2012;Nepal et al, 2020;Rock et al, 1989;Tang et al, 2014;Zheng et al, 2014). However, other studies demonstrated no significant association between pro-inflammatory cytokine concentration and AMS incidence (Lundeberg et al, 2018;Swenson et al, 1997).…”
Section: Acute Mountain Sickness and Inflammatory Marker Expressionmentioning
confidence: 99%